The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1016/s0921-4526(99)01199-0
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism in single-crystalline CePtSn

Abstract: CePtSn exhibits two antiferromagnetic transitions at low temperatures. We report on mae~etoresistance and inabmetization studies of single-crystalline CePtSn in magnetic fields up to 18 T. The data were taken to estiblish the magnetic phase diagrams for CePtSn in fields applied along the principal directions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…CePtSn exhibits also an order-to-order magnetic phase transition at T M =5.0 K. At low temperatures (To2 K) a metamagnetic transition (MT) occurs at BB3 T applied along the b-axis. It is accompanied by an irreversible negative GMR effect [3]. Neutron diffraction experiments revealed that changes in population of two types of AF domains with different resistivity characteristics are responsible for the GMR effect [4].…”
mentioning
confidence: 99%
“…CePtSn exhibits also an order-to-order magnetic phase transition at T M =5.0 K. At low temperatures (To2 K) a metamagnetic transition (MT) occurs at BB3 T applied along the b-axis. It is accompanied by an irreversible negative GMR effect [3]. Neutron diffraction experiments revealed that changes in population of two types of AF domains with different resistivity characteristics are responsible for the GMR effect [4].…”
mentioning
confidence: 99%